THE PRICE OF REPUTATION IN THE CZECH REPUBLIC - Vejvodová, Veronika (2012)
In my thesis I observe the effect of reputation on the final price of the product through internet auction portal AUKRO.cz. With 140 finished auctions through the "matching method" I observed that higher rated seller gain an average price premium of 16% over a seller with lower reputation, in the condition when the sellers offered almost similar products. The research also exerts effort to describe people's behaviour and incentives according to particular condition including the reputation. By examining the positive dependence between reputation and price premium, this work highlights the need to build up and hold the high reputation score.